Budaya Urban Muslim Kelas Menengah - Rofhani, Rofhani (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article will discuss the cultural dimension is understood in the conventional sense, ie as beliefs, values, and a person?s lifestyle in everyday life. In addition, this article will examine the cultural phenomenon of the modern (or even postmodern) is by some regarded as an ethical culture that reduces the value of the community. These conditions then led to the birth of fundamentalism that offer Islamic culture. But in its development, this solution has not quite accepted by the Muslim urban middle class, as assessed ancient cultures offer, traditional or even outmoded, but on the other hand they also indicate a negation of the Western culture which is considered to damage the image of Muslims. Therefore, this group tried to make a synthesis of culture with other cultures raises and offering style that still offers a more modern Islam and not obsolete.